Lower level noise exposure that produces only TTS modulates the immune homeostasis of cochlear macrophages - Frye, Mitchell D. (J Neuroimmunol, 2018)
Noise exposure producing temporary threshold shifts (TTS) has been demonstrated to cause permanent changes to cochlear physiology and hearing function. Several explanations have been purported to underlie these long-term changes in cochlear function, such as damage to sensory cell stereocilia and synaptic connections between sensory cells and their innervation by spiral ganglion neurons, and demyelination of the auditory nerve. Though these structural defects have been implicated in hearing difficulty, cochlear responses to this stress damage remains poorly understood. Here, we report the activation of the cochlear immune system following exposure to lower level noise (LLN) that causes only TTS. Using multiple morphological, molecular and functional parameters, we assessed the responses of macrophages, the primary immune cell population in the cochlea, to the LLN exposure. This study reveals that a LLN that causes only TTS increases the macrophage population in cochlear regions immediately adjacent to sensory cells and their innervations. Many of these cells acquire an activated morphology and express the immune molecules CCL2 and ICAM1 that are important for macrophage inflammatory activity and adhesion. However, LLN exposure reduces macrophage phagocytic ability. While the activated morphology of cochlear macrophages reverses, the complete recovery is not achieved 2 months after the LLN exposure. Taken together, these observations clearly implicate the cochlear immune system in the cochlear response to LLN that causes no permanent threshold change.